Financial performance, intellectual capital disclosure and firm value: the winning edge - Charles Kiprono Sang Keter; Josephat Yegon Cheboi; David Kosgei (Cogent Business & Management, 2024)
Traditional financial performance metrics have served well throughout the inclusion era, but they are no longer in sync with the skills and competitiveness that organizations are attempting to learn. This study examined the role of intellectual capital disclosure (ICD) in mediating the relationship between financial performance and firm value. The sample consists of 39 firms listed on the Nairobi Securities Exchange (NSE) in Kenya. They represent 67% of firms listed on NSE during the period (2010–2022). Data were extracted from individual companies' audited annual reports. The study hypotheses were tested on a fixed and random effects model with the aid of the Stata student version. The results reveal that financial performance has a positive and significant effect on firm value. Furthermore, financial performance has a negative effect on ICD. Finally, ICD was found to have a mediating effect on the relationship between financial performance and firm value. The results confirm that intellectual capital disclosure is an important mediator in the relationship between financial performance and firm value; firm managers should use ICD as a winning edge. Additionally, firms with high intellectual capital are likely to engage in voluntary disclosure to legitimize their success.The study examine whether or not listed companies' disclosure of intellectual capital is value-relevant in share markets? The difference between a high-, average-, or mediocre-valued firm is not a huge difference in the ability of the CEO, but a few small things done consistently and repeatedly, such as the presentation of intangible assets in financial reports. Thus, organizations disclose intellectual capital to legitimize their success away from the traditional symbol of firm success based on tangible resources.
Keywords: G40; 650; Financial performance (FP); intellectual capital disclosure (ICDs); firm value (FV); Tobin's Q index